so this is how you solve it
x years ago
Bill was 60-x
Hill was 42-x.
Bill's age equal 12 less than twice Hill's age
60 - x = 2(42-x)-12
60 - x = 84 - 2x -12
60 - x = 72 - 2x
x = 12
2007-01-05 08:11:56
·
answer #1
·
answered by ella 3
·
0⤊
0⤋
x years ago, Bill was 60-x and Hill was 42-x. So...
Bill's age equal 12 less than twice Hill's age
60 - x = 2(42-x)-12
60 - x = 84 - 2x -12
60 - x = 72 - 2x
x = 12
2007-01-05 07:21:33
·
answer #2
·
answered by Professor Maddie 4
·
0⤊
0⤋
let before x years Bill,s age equal to 12 less than twice Hill,s age
(60-x)=2(42-x)-12
60-x=84-2x-12
2x-x=84-12-60
x=12
then before 12 years
Bill,s age=60-12=48 years
Hill,s age =42-12=30 years
2007-01-05 07:31:44
·
answer #3
·
answered by eissa 3
·
0⤊
0⤋
It's not exactly clear if you meant 12 less or 1/2 less. 12 less than twice Hill's age is 72 and Bill's not there yet, so I guess you mean 1/2.
1/2 less than twice Hill's age is 42. 60 - 42 = 18, therefore, it would be 18 years ago.
2007-01-05 07:47:47
·
answer #4
·
answered by Anonymous
·
0⤊
0⤋
60 -x = 2(42-x) - 12
60 - x = 84 - 2x - 12
60 - x = 72 - 2x
x = 12
Check:
12 years ago, Bill was 48 and Hillary was 30. Twice 30 is 60, 12 less is 48. Voila!
Answer is 12 years ago.
Did you choose the names on purpose? Where does Chelsea fit into the equation?
2007-01-05 07:17:03
·
answer #5
·
answered by jenh42002 7
·
0⤊
0⤋
B=60
H=42
B-X=(2 x [H - X]) - 12
60 - X = 2 x [42 - X] - 12
60 - X = 2 x 42 - 2X - 12
60 - X = 84 - 12 - 2X
60 - X = 72 - 2X
X + [60 - X] = X + [72 - 2X]
60 + [X - X] = [X - 2X] + 72
60 = X + 72
-72 + 60 = -72 + X + 72
-12 = X + [-72 + 72]
X = -12
12 years ago.
2007-01-05 07:29:41
·
answer #6
·
answered by flyddw 2
·
0⤊
0⤋
Let the answer be x.
So 60-x is 12 less than 2*(42-x), or 60-x=2(42-x)-12.
60-x=84-2x-12
60-x=72-2x
-x=12-2x
0=12-x
x=12
So the answer is 12.
2007-01-05 07:18:14
·
answer #7
·
answered by Adam 2
·
0⤊
0⤋
12 years ago... Bill will be 48 and Hill will be 30.
2007-01-05 07:23:41
·
answer #8
·
answered by Tommy R 2
·
0⤊
0⤋
b=60
h=42
x= # of years ago
b-x=2(h-x)-12
60-x=2(42-x)-12
60-x=84-2x-12
60-x=72-2x
-x+2x=72-60
x=12 so it was 12 years ago.
check
60-12=48
2(42-12)=2*30=60
60-12=48
2007-01-05 07:19:32
·
answer #9
·
answered by yupchagee 7
·
0⤊
0⤋
60b - 42h = 2h - 12
2007-01-05 07:17:04
·
answer #10
·
answered by Anonymous
·
0⤊
0⤋